Familial hypercholesterolemia class II low-density lipoprotein receptor response to statin treatment - Linda Omer; Lubna Hindi; Giuseppe Militello; Katlin B. Stivers; Kenneth C. Tien; Nolan L. Boyd (The Company of Biologists, 2020)
Low-density lipoprotein (LDL) receptor (LDLR) mutations are the primary cause of familial hypercholesterolemia (FH). Class II LDLR mutations result in a misfolded LDLR retained in the endoplasmic reticulum (ER). We have developed a model of FH class II and CRISPR-corrected induced pluripotent stem cells (iPSC) capable of replicating mutant and repaired LDLR functions. We show here that iPSC and derived hepatocyte-like cells (HLC) replicate misfolded LDLR accumulation and restoration of LDLR function in CRISPR-corrected cells. It was reported that model cells overexpressing class II LDLR mutants result in endoplasmic reticulum (ER) accumulation of immature LDLR and activation of the unfolded protein response (UPR). We show here that statins induce a similar accumulation of immature LDLR that is resolved with class II correction. We also demonstrate that, although capable of UPR induction with tunicamycin treatment, unlike overexpression models, statin-treated class II iPSC and derived HLC do not induce the common UPR markers Grp78 (also known as HSPA5) or spliced XBP1 [XBP1 (S)]. Because statins are reported to inhibit UPR, we utilized lipoprotein-deficient serum (LPDS) medium, but still did not detect UPR induction at the Grp78 and XBP1 (S) levels. Our study demonstrates the recapitulation of mutant and corrected class II LDLR function and suggests that overexpression models may not accurately predict statin-mediated class II protein biology.